2008
DOI: 10.1515/cclm.2008.067
|View full text |Cite
|
Sign up to set email alerts
|

5′ ins/del and 3′ VNTR polymorphisms in the apolipoprotein B gene in relation to lipids and coronary artery disease

Abstract: The two polymorphisms exert an impact on lipid levels and contribute to the susceptibility to the development of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…M/L carriers had TC, LDL-C, and apoB concentrations significantly higher than those of S/S, S/M, S/L, or M/M carriers, and individuals with the L allele accordingly exhibited TC, LDL-C, and apoB levels significantly higher than those with M or S alleles. These results were consistent with those of other investigators (Hansen et al, 1993;Pan et al, 1998;Rebhi et al, 2008). However, in children with PNS, no significant differences in serum lipid levels were observed for variant genotypes and alleles of the apoB 3' VNTR.…”
Section: Discussionsupporting
confidence: 93%
“…M/L carriers had TC, LDL-C, and apoB concentrations significantly higher than those of S/S, S/M, S/L, or M/M carriers, and individuals with the L allele accordingly exhibited TC, LDL-C, and apoB levels significantly higher than those with M or S alleles. These results were consistent with those of other investigators (Hansen et al, 1993;Pan et al, 1998;Rebhi et al, 2008). However, in children with PNS, no significant differences in serum lipid levels were observed for variant genotypes and alleles of the apoB 3' VNTR.…”
Section: Discussionsupporting
confidence: 93%
“…In this study we did not measure APOB level in serum to correlate with 3ʹ-VNTR repeat numbers in diabetic and non-diabetic individuals. Earlier studies have reported high APOB protein level in serum of individuals with larger APOB 3ʹ-VNTR alleles 18,36,37 . In Canadian aboriginal people, high level of plasma APOB protein was found to be associated with type 2 diabetes as well as a better predictor of risk compared to LDL or HDL cholesterol 12 .…”
Section: Discussionmentioning
confidence: 88%
“…Alleles with higher repeats (≥36 repeats) were shown to be strongly correlated with coronary heart disease 18,[33][34][35] . APOB 3ʹ-VNTR alleles with higher repeats are also significantly associated with higher levels of total cholesterol (TC) and low density lipoprotein-cholesterol (LDL-C) 36,37 . Kanani et al detected raised APOB protein in 56.7% of the type 2 diabetics 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the included studies are listed in Table (1a, 1b, 1c, 1d, in Supplementary document). A total of 47 eligible studies (Aburatani et al 1987;Al-Bustan et al 2009;Anghebem-Oliveira et al 2009;Beneš et al 2000a, b;Berkinbayev et al 2014;Bohn et al 1993Bohn et al , 1994Buraczynska et al 2000;Corbo et al 1997;De Lorenzo et al 1993;de Padua Mansur et al 2000;Duman et al 2005;Dunning et al 1993;Ferns and Galton 1986;Gallegos-Arreola et al 2012;Gardemann et al 1998;Genest et al 1990;Hegele et al 1986;Hong et al 2001;Hosking et al 1992;Huang et al 2012;Kallel et al 2008;Machado et al 2001;Marshall et al 1994;Mendis et al 1991;Miettinen et al 1994;Myant et al 1989;Nieminen et al 1992;Pan et al 1995;Paulweber et al 1990;Rebhi et al 2008;Saha et al 1992;Salazar et al 2000;Scartezini et al 2003;Stepanov et al 1998;Tybjaerg-Hansen et al 1991;Visvikis et al 1993;Wiklund et al 1989;Wu et al 1994;Xu and Zhou 1998;…”
Section: Characteristics Of the Eligible Studiesmentioning
confidence: 99%